TINJAUAN HUKUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 DALAM MENJAMIN PERLINDUNGAN HAK KONSTITUSIONAL MASYARAKAT - Yoga Siwananda; Widnyana, I Made Adi; Sugita, I Made (VYAVAHARA DUTA, 2024)
Elections are an important tool in realizing democracy and popular sovereignty. However. This triggered a lawsuit to the Constitutional Court (MK) to test the constitutionality of norms that were considered contrary to the 1945 Constitution of the Republic of Indonesia. Decision Number 90/PUU-XXI/2023 which regulates the age limit of presidential and vice presidential candidates After the Constitutional Court's decision, Article 169 letter q of the Election Law was amended by adding the phrase "or has / is currently holding an office elected through general elections including regional head elections". This decision has drawn pros and cons because it is considered to open up opportunities for young politicians to advance in the electoral contestation, but on the other hand it is feared that it will result in a lack of experience and capability in leading the nation. The purpose of this study is to examine and analyze the legal review of the Constitutional Court's decision Number 90/PUU-XXI/2023 in the perspective of comparison with other legal provisions and to find out and analyze the legal implications arising from the Constitutional Court's decision Number 90/PUU-XXI/2023 in guaranteeing people's constitutional rights. This research uses normative research methods with a doctrinal juridical approach. Research data is obtained through literature studies, namely primary and secondary legal materials relevant to the research topic. This research uses judicial theory, legal state theory, and democracy theory as the basis for analyzing the Constitutional Court's decision and its implications for people's constitutional rights. The results of this study show that this decision is in accordance with the constitution and legal principles applicable in Indonesia. Strengthening the people's political rights to elect and be elected to run for president and vice president. Thus, upholding the principles of equality and justice in the democratic process. Other countries have provided opportunities for every citizen under the age of 40 to participate in running for president and vice president as regulated in the laws of each country. The implications of the Constitutional Court's decision number 90/PUU-XXI/2023 give hope to young people or regional heads who are under the age of 40 to participate in the contestation of the election of the president and vice president of the Republic of Indonesia.